Effects of Solid-State Fermentation with the Ganoderma spp. and Coriolus versicolor on the Total Phenol Contents and Antioxidant Properties on Black Soybean - Yanting Li; Lina Xu; Shang Guo (Journal of Chemistry)
Aim of this study was to evaluate the influence of solid-state fermentation of 4 strains ((Ganoderma oregonense (GO), Ganoderma lucidum (GL), Ganoderma sinensis (GS), and Coriolus versicolor (CV))) on the nutrients, functional ingredients, and antioxidant activity in black soybean. As a result, after fermentation by 3 strains of Ganoderma spp. and CV, the contents of crude protein, crude fat, reducing sugar, soluble protein, triterpenoid, and total phenol contents in black soybean significantly increased P < 0.01, particularly in CV-black soybean. The contents of crude protein, crude fat, reducing sugar, soluble protein, and total phenol were 122.92%, 132.69%, 290.08%, 122.58%, and 142.47% higher than those of the control groups, respectively. But the total sugar and crude fiber contents decreased significantly P < 0.01. Furthermore, analysis of antioxidant capacity showed that all the fermented products had scavenging effects on DPPH, hydroxyl, and superoxide anion radicals. In addition, the DPPH scavenging ability of CV fermented products was highest, the hydroxyl radical scavenging ability of GS fermented products was highest, and the superoxide anion radical scavenging ability of GO fermented products was highest, which were 9.43, 7.65, and 3.39 folds higher than those of control groups, respectively. All results evidenced that the fermented strains and the fermented time had remarkable influences on the nutritional ingredient and antioxidant activity of fermented products in black soybean. Also, there was a significant correlation between total phenolic content and antioxidant activities. In conclusion, fermented black soybean with fungus has the potential to be developed into a functional food and nutraceutical material.